2014
DOI: 10.1002/2013gb004765
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on rates of ammonium uptake and nitrification in the western coastal Arctic during winter, spring, and summer

Abstract: Biogeochemical rate processes in the Arctic are not currently well constrained, and there is very limited information on how rates may change as the region warms. Here we present data on the sensitivity of ammonium (NH 4 + ) uptake and nitrification rates to short-term warming. Samples were collected from the Chukchi Sea off the coast of Barrow, Alaska, during winter, spring, and summer and incubated for 24 h in the dark with additions of 15 NH 4 + at À1.5, 6, 13, and 20°C. Rates of NH 4 + uptake and nitrifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 82 publications
6
50
0
1
Order By: Relevance
“…Lower ∆ 17 O NO3 values than the atmospheric end‐member indicate the co‐existence of another NO 3 − source, with Δ 17 O = 0‰ (Figures f and S2c). The remaining NO 3 − in sea ice is ostensibly biologically sourced, produced by nitrification (the oxidation of NH 4 + and/or NO 2 − ) that occurred in sea ice directly (e.g., Baer et al, , ; Fripiat et al, , ), and/or in seawater before its incorporation into sea ice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lower ∆ 17 O NO3 values than the atmospheric end‐member indicate the co‐existence of another NO 3 − source, with Δ 17 O = 0‰ (Figures f and S2c). The remaining NO 3 − in sea ice is ostensibly biologically sourced, produced by nitrification (the oxidation of NH 4 + and/or NO 2 − ) that occurred in sea ice directly (e.g., Baer et al, , ; Fripiat et al, , ), and/or in seawater before its incorporation into sea ice.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there are no other observations of δ 15 N NH4 or δ 15 N PN in sea ice or snow from the Arctic region to compare with our results, but the δ 15 N PN in bottom ice in this study (2.1 to 4.3‰) covers a comparable range to that in spring Antarctic sea ice (1.1 to 4.4‰ (Fripiat et al, 2014) and <5‰ (Fripiat et al, 2015)). ) that occurred in sea ice directly (e.g., Baer et al, 2014Baer et al, , 2015Fripiat et al, 2014Fripiat et al, , 2015, and/or in seawater before its incorporation into sea ice.…”
Section: Global Biogeochemical Cyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…The nitrification rate in the Arctic Ocean has been reported only in the Chukchi Shelf region, namely, the surface layer (<50 m;Baer et al, , ; Christman et al, ; Shiozaki et al, ). Nitrification rates in surface water (0–6.5 m) are reported to be below ~1 nmol N L −1 day −1 (Christman et al, ; Baer et al, , ; Shiozaki et al, ), which is consistent with our results. We found a similar vertical distribution of the nitrification rate to that in a previous study in the Chukchi shelf (Shiozaki et al, ), with the maximum value occurring near the bottom, where the ammonium concentration was also high (5.5 μmol/L).…”
Section: Discussionmentioning
confidence: 99%
“…In this section, we include only light intensity in our discussion of the light effect on nitrification. Arctic warming is evident in recent climate data (Cohen et al, 2014;Serreze & Francis, 2006), but nitrification in the Arctic Ocean is reported to be insensitive to temperature change (Baer et al, 2014). This finding is probably due to AOOs in the oceanic environment generally being adapted to the large temperature changes that occur in their environments (Horak et al, 2013;Ward, 2008).…”
Section: Factors Controlling the Nitrification Rate In The Arctic Oceanmentioning
confidence: 99%